GEOPOLITICS OF MEDITERRANEAN REGION - Zafar, Javed (Indonesian Journal of International Relations, 2024)
The present paper will discuss the contemporary geopolitical setting of the Mediterranean region. This paper will examine how different powers, including Europe and Asia, are struggling to influence the Mediterranean strategic space. The paper will also discuss how the region is emerging as an alternative to Russian energy for Europe. Turkey is an important stakeholder and player in the Mediterranean region. Turkey has multiple interests, including cultural, economic, and strategic; therefore, the country is serious about its engagements in the region. The paper also focusses on how Turkey has been managing its interests in the region. The paper is based on descriptive and analytical research methods. The historically Mediterranean region always plays an important role in global geopolitics. The region is important for NATO. In the post-Cold War era, new coalitions were made in the region. Ukraine's war makes the region more important. Turkey is restructuring its strategy in the region